Persepsi dan Kecenderungan Keterlibatan Apoteker di Apotek pada Proses Rekonsiliasi Obat - Eko Setiawan; Sylvi Irawati; Bobby Presley; Susilo Ari Wardhani (Jurnal Sains Farmasi & Klinis, 2015)
The objective of this study was to gain insight into the perception and the likelihood to practice medication reconciliation among pharmacists working at the apotek. Two guiding questions were given to each participant and participants were asked to write the answer on the paper. Thematic analysis was used to analyse the data. There were 31 pharmacists involved in this study. All of participants perceived that medication reconciliation was important to be implemented. Almost all of participants (i.e 30 from 31 pharmacists) clearly stated that they would like to implement medication reconciliation. And, there were 3 themes found as the main motivation factors in implementing the medication reconciliation. Pharmacists who were working at the apotek had a good perception about medication reconciliation and also showed the likelihood to implement medication reconciliation. Further research need to be conducted in order to explore the barriers in implementing medication reconciliation.